Comparative characteristics of antiarrhythmic and anticonvulsive properties of some derivatives of 7-alkyl-8-piperazine-3-methylxanthine - Samura, I. B.; Muteto, Dale; Siangshai, Arwada; Самура, Ірина Борисівна (Запорізький державний медичний університет, 2018)
Methylxanthines of natural and synthetic origin are of biological and pharmacological interest. In dependence on the kind and place of substitution in one of xanthine rings, a large variety of pharmacological activities were reported. The purpose of the paper was investigation of antiarrhythmic and anticonvulsive activity of some newly synthesized derivatives of 7-alkyl-8-piperazine-3-methylxanthine [compounds 1-7]. The investigated compounds were tested for their effect on the heart (protection against adrenaline, aconitine, strophanthin and calcium chloride induced arrhythmias), as well as anticonvulsive activity. Antiarrhythmic activity has been investigated in anaesthetized with nembutal-sodium (30 mg/kg) young male rats of Vistar line with mass 180-220 g. Arrhythmias were modelled by IV administration of adrenaline hydrochloride (250 mg/kg), aconitine (40 mcg/kg), calcium chloride (250 mg/kg) and strophanthine (200 mg/kg). Investigate compounds were administered intraperitoneally (prophylactic action) and intravenously (therapeutic action) in a dose 0.05 LD50. Procainamide in a dose of 20 mg/kg was used as a standard preparation.
Keywords: тези доповідей